Logistics in Yemen: Addressing the Weakness of Purchasing Power to Satisfy Needs: In Context of Supply Chain Design Optimization (Case of Yemen) - Najeeb, Hisham; Raju, Valliappan; Rahman, Shafiqur (ExcelingTech, 2019)
The purchasing power in Yemen is gradually decreasing due to the increase in products cost and required an instant solution to meet the demand of the consumers. increase in energy prices and continuous inflation of the national currency presents several challenges to manufacturer interested in competing in the local market, in order to keep up with the market they should make changes that make improvements in products etc. low-cost package, production, and transportation a top priority for product development. In this research study the author attempt to use quantitative and qualitative research method, plan and execute fieldwork, collecting data form products’ local market, local factories (Arwa plastic industry), the ministry of industry & trade, etc. in Yemen, during fieldwork. During data collection and fieldwork, the author will visit the ministry of industry and trade to meet the representative to get the requested data of local industries and imports of raw materials for products packaging, then the author will visit capital city of Yemen (Sana’a) ,Taiz and Hodeida industrial zones to meet the representative of local factories to collect the data of products’ packaging raw materials along with the local market, after that the author will visit a local plastic production factory (Arwa plastic industry ltd) to support the study of changing over from rigid heavy packaging to adaptable packaging . The author will also prepare a research questionnaire for manufacturer and customers to substantiate the research with evidence. Finally, the author will visit Yemen General Union of heavy Transport, to collect data of road freight. Finally, after collecting required data, the author will analyse and identify the extent of the manufacturer ability to switch from traditional heavy packaging’s to the most convenient product in terms of weight, ease of manufacturing without the need for a lot of energy, In addition to its lightweight suitable to provide less transport value and space because of the flexibility of the product as well as the extent to which the customer accepts the new product that suits his income and expectations, also preserving the environment from pollution. After analysing data and identifying findings, the author found that if the manufacturer shift to flexible, lightweight products’ packages can reduce fright and storage costs significantly as well as retail prices.